2020
DOI: 10.1021/acs.energyfuels.0c00682
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Development of Sorbents for Calcium Looping

Abstract: The calcium looping (CaL) process is a promising CO 2 capture technology, which uses CaO-based sorbents by employing a reversible reaction between CaO and CO 2 , generally named carbonation and calcination for each direction of the reaction. Although CaO-based sorbents possess many advantages, including wide availability, relatively low cost, and high theoretical CO 2 uptake (∼0.786 g of CO 2 /g of CaO), it mainly suffers from a rapid decline in CO 2 capture performance during cyclic operation, which has remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 263 publications
0
86
0
Order By: Relevance
“…Reported activation energies for the carbonation reaction are low and typically < 30 kJ mol -1 , often ~ zero [97]- [99]. Various conceptually different reaction models were found suitable for the kinetic modelling of the carbonation reaction [46], [96], [100], including shrinking core, pore and grain models. Similar to many gas-solid reactions, the observed rate of carbonation decreases once all readily available surface CaO has been covered with a product layer of CaCO3.…”
Section: Cao-caco3 Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported activation energies for the carbonation reaction are low and typically < 30 kJ mol -1 , often ~ zero [97]- [99]. Various conceptually different reaction models were found suitable for the kinetic modelling of the carbonation reaction [46], [96], [100], including shrinking core, pore and grain models. Similar to many gas-solid reactions, the observed rate of carbonation decreases once all readily available surface CaO has been covered with a product layer of CaCO3.…”
Section: Cao-caco3 Systemmentioning
confidence: 99%
“…The following two subsectionsdealing with stabilizers that alternatively do not or do form mixed phases with CaO or CaCO3review recent works that have led to a better understanding of how stabilizers function within a sorbent; for a comprehensive list of works on synthetic sorbents we refer to some recent reviews on the topic [44]- [46], [360].…”
Section: Structural Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of concentrated CO 2 atmospheres approximating realistic industrial CaL calcination conditions for generating an exit gas stream with a high concentration of CO 2 is still a challenge [3], and the sorbents are rarely tested using laboratory scale reactors under severe regeneration calcination conditions. In a recent review focused on the development of sorbents for CaL, only~6% of experimental tests were performed under high CO 2 concentration using laboratory scale reactors [52]. In our previous work, it was shown that WMP are promising waste materials to be used as sorbents for CaL, but the calcination was carried out under a mild calcination atmosphere (N 2 , 800 • C).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon capture and utilization technologies are widely acknowledged as the most important approaches that can reduce CO 2 emissions and supply fuel-related products [1][2][3][4]. The use of natural limestone as multicyclic absorbent is an attractive option for the separation of CO 2 from flue gases due to its high CO 2 capture capacity, high carbonation temperature, easy availability, and relatively low cost [5][6][7]. However, because the operating temperature of calcium looping is higher than the Tammann temperature of CaCO 3 [8,9], and the adsorption/desorption process of CO 2 has a catalytic effect on CaO sintering [10,11], the CO 2 capture capacity of calciumbased sorbents reduces rapidly after only a few carbonate looping cycles [12,13].…”
Section: Introductionmentioning
confidence: 99%